Firm Size, Good Corporate Governance, Capital Structure, and Financial Performance: Evidence from Food and Beverage Manufacturing Companies during 2021–2025 - Romiyatun Romiyatun; Sunarto Sunarto (STIE Amkop Makassar, 2026)
This study was conducted to examine the effect of firm size, good corporate governance, and capital structure on financial performance in food and beverage manufacturing companies. This research employed a descriptive quantitative method using secondary data obtained from the financial statements of companies listed on the Indonesia Stock Exchange (IDX). The population consisted of 83 companies, while 24 companies were selected as the research sample using the purposive sampling technique. The results of this study indicate that firm size has a positive and significant effect on financial performance. Good Corporate Governance, proxied by independent commissioners, has no significant effect on financial performance. Meanwhile, capital structure has a positive and significant effect on financial performance.